PENGEMBANGAN BUKU TIGA DIMENSI UNTUK PEROLEHAN BELAJAR KONSEP STRUKTUR DAN FUNGSI SEL - Supartini, Sri; Asrori, Asrori; Aswandi, Aswandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This study aims to: 1) Design the prescriptions of learning tasks that are contained in three-dimensional book media structure and cell functions. 2) Describe the three-dimensional book designing media techniques for cell structure and function. 3) Generate three-dimensional book media display of cell structure and function. 4) Know the acquisition of learning structure and cell function after using the media of three-dimensional book (Pop up book). This research type is research and development with quantitative approach. The research samples used random sampling technique in homogenous population in class XI MIPA 1, XI MIPA 2, XI MIPA 3, XI MIPA 4, XI MIPA 5, XI MIPA 6, XI MIPA 7, XI MIPA 8, and XI MIPA 9. Random sampling technique obtained by one class as research sample that is class XI MIPA 8 SMA Negeri 1 Pontianak. The results of the research are: 1) Learners become very helpful in understanding the concept of cell structure and function in the presence of learning scenarios that contain learning tasks that reflect the scientific approach stages; observing, questioning, collecting data, associating and communicating - as prescriptions of learning tasks. 2) The three-dimensional book is designed based on the learners' needs analysis aimed at solving learning problems. 3) The learners' enthusiasm in the study of cell material can be raised and motivated by a three-dimensional book view of cell structure and function. 4) The acquisition of learning the concept of cell structure and function increases as a result of the three-dimensional book. This can be seen from the results of t-test calculations. In the final stages of data analysis is the value of t arithmetic equal to -9.161 with Sig 0.000. Because Sig <0.05 can be concluded that the use of three-dimensional book structure and cell function can improve learning achievement learners. Keywords: Three-Dimensional Books, Acquisition of Learning Concepts of Cell Structure and Function